Design of Feedback Control for Networked Finite-Distributed Delays Systems with Quantization and Packet Dropout Compensation - Wen-Chiung Hsu; Lian-Wang Lee; Kuan-Hsuan Tseng; Chien-Yu Lu; Chin-Wen Liao; Ho-Nien Shou (Discrete Dynamics in Nature and Society)
This paper investigates the feedback control for networked discrete-time finite-distributed delays with quantization and packet dropout, and systems induce the H∞ control problem. The compensation scheme occurs in a random way. The quantization of system state or output signal is in front of being communicated. It is shown that the design of both a state feedback controller and an observer-based output feedback controller can be achieved, which ensure the asymptotical stability as well as a prescribed H∞ performance of the resulting closed-loop system satisfying dependence on the size of the discrete and distributed delays. Numerical examples are given to illustrate the effectiveness and applicability of the design method in this paper.